Phage DisCo: targeted discovery of bacteriophages by co-culture - Eleanor A. Rand; Natalia Quinones-Olvera; Kesther D. C. Jean; Carmen Hernandez-Perez; Siân V. Owen; Michael Baym (mSystems)
ABSTRACT Phages interact with many components of bacterial physiology from the surface to the cytoplasm. Although there are methods to determine the receptors and intracellular systems a specified phage interacts with retroactively, finding a phage that interacts with a chosen piece of bacterial physiology a priori is very challenging. Variation in phage plaque morphology does not to reliably distinguish distinct phages, and therefore many potentially redundant phages may need to be isolated, purified, and individually characterized to find phages of interest. Here, we present a method in which multiple bacterial strains are co-cultured on the same screening plate to add an extra dimension to plaque morphology data. In this method, phage discovery by co-culture (Phage DisCo), strains are isogenic except for fluorescent tags and one perturbation expected to impact phage infection. Differential plaquing on the strains is easily detectable by fluorescent signal and implies that the perturbation made to the surviving strain in a plaque prevents phage infection. We validate the Phage DisCo method by showing that characterized phages have the expected plaque morphology on Phage DisCo plates and demonstrate the power of Phage DisCo for multiple targeted discovery applications, from receptors to phage defense systems.IMPORTANCEIn this work, we describe a targeted phage discovery method that allows immediate isolation of phages with specific traits. Currently, to find a phage with specific properties, huge libraries of phages must be collected and screened retroactively. This assay, Phage Discovery by Co-culture (Phage DisCo), works by co-culture of host strains that are identical except for one perturbation that may interfere with phage infection and a unique fluorescent marker. These strains are co-cultured with an environmental sample of interest in traditional plaque assay format, making phage characteristics easily identifiable by fluorescent signal after imaging of the screening plate. We validate that Phage DisCo can identify phages with specific properties, even when these phages are rare in samples. This approach allows rapid exploration of the diversity within phage samples with vastly streamlined processes, and we anticipate it will be widely adopted within the phage discovery field.